Strengthening Malaysian District Education Offices as learning organizations through change indicators - Mohd Izham Mohd Hamzah; Nurul Sahadila Abd Rani (Penerbit Universiti Kebangsaan Malaysia, 2020)
The District Transformation Program (DTP) aims to accelerate school improvement through a program led by the District Education Office (DEO). This mixed method study determined the relationship between strengthening processes and change indicators, the impacts of strengthening processes on change indicators, as well as identified the change indicators in the context of strengthening the DEOs. A total of 93 DEO heads were surveyed using an adapted questionnaire, and semi-structured interviews were done involving six participants. It was found that there is a strong positive relationship between strengthening processes and change indicators. The highest predictor that contributed to the change indicator in the DEO were support, followed by source, and accountability dimensions. Qualitative findings revealed nine change indicator themes in DEOs, which were the roles and responsibilities of DEO Heads, Program Managers, School Improvement Partners+, and School Improvement Specialist Coaches+, Performance Dialogue, Allocation Management, Key Performance Index, Performance Dashboard and DEO Excellence Rating. The implications of this study can be used in DEO monitoring and as an early intervention to detect existing issues in the implementation of the change program. In-depth studies to explore the factors that influence the success of changes in the practice of the DEO as a learning organization is recommended.